(untitled) (Journal of the College of Basic Education, 2026)
One of the issues that has attracted the attention of exegetes in general is the question of human intention in committing an error and its impact on divine punishment. This issue is fundamentally grounded in examining the dialectical relationship between the nature of divine justice and mercy in dealing with the erring individual, and in understanding how divine punishment is accordingly determined. Exegetes have differed in their interpretations of this problem, adopting various methodological approaches in an attempt to provide an inferential explanation that contributes to resolving the conceptual difficulty of understanding this duality, while maintaining consistency with the principle of divine justice in the ordering of punishments. This inquiry is undertaken through a comparative analysis of textual models: the context of the verses in Surat al-Baqarah concerning the plea of the erring individual not to be held accountable for mistakes and forgetfulness resulting from negligence or improper intent, and the account of Uzzah’s punishment in the Second Book of Samuel, which serves as a practical example presented in the Old Testament. This comparison elucidates the principle of the dual relationship between the transgression of a divine command and the role of mistaken or forgetful intent.